Heavy ion radiotherapy during pregnancy - Münter, Marc; Wengenroth, Marc; Fehrenbacher, Georg; Schardt, Dieter; Nikoghosyan, Anna; Durante, Marco; Debus, Jürgen (Fertility and sterility, 2010)
Objective - To provide a safe particle therapy treatment for a pregnant woman with skull-base cancer. - Design - Case report. - Setting - University clinic. - Patient(s) - A 27-year-old woman diagnosed for a skull-base chordoma and whose pregnancy was found during the course of radiotherapy with accelerated carbon ions. - Intervention(s) - Therapy was continued as scheduled, and fetal dose produced by photons and neutrons was measured at each radiotherapy fraction using passive and active monitors. - Main Outcome Measure(s) - Radiation dose to the uterus. Health of the mother and the newborn. - Result(s) - Total dose to the uterus was <0.2 mSv. About 30% of this dose was caused by neutrons. Magnetic resonance imaging of the skull base showed no evidence of recurrent disease in the mother. The child was healthy with normal development. - Conclusion(s) - Heavy ion cancer therapy produces a very low dose in distal organs.
Gesehen am 11.05.2023